E-165 Carotid intraplaque hemorrhage is independent of the degree of carotid artery stenosis and is more prevalent in symptomatic versus asymptomatic patients with stenosis less than 70%: implications for the utility of carotid plaque imaging. (4th August 2020) - Larson, A; Benson, J; Lanzino, G; Brinjikji, W
Abstract : Background: The relationship between the prevalence of intraplaque hemorrhage and degree of carotid artery stenosis has not been well established. It is unclear whether there is a threshold of stenosis/plaque progression during which plaque hemorrhage develops within an atherosclerotic lesion. Methods: In this study, we reviewed our institutional case series of patients with carotid plaque imaging and reported on the prevalence of plaque hemorrhage based on degree of stenosis as well as symptomatic status. Results: The presence of plaque hemorrhage was independent of degree of stenosis. This was true among both asymptomatic carotid arteries (P=0.31) and symptomatic carotid arteries (P=0.11). For arteries with severe stenosis, there was no difference in prevalence of plaque hemorrhage among symptomatic and asymptomatic patients (22/69 versus 10/40, P=0.52). However, for arteries with moderate stenosis (30–69%) the prevalence of plaque hemorrhage was significantly higher among symptomatic arteries versus asymptomatic (31/69 versus 10/66, P=0.0002). The same was true for patients with no stenosis (17/176 versus 6/504, P<0.0001). Conclusions: The presence of plaque hemorrhage is independent from the degree of carotid artery stenosis. Carotid Plaque Imaging for detection of plaque hemorrhage is likely most helpful in identifying symptomatic lesions among patients with <70% stenosis. Its utility for patients with severe stenosis is less certain. Disclosures: A. Larson: None. J. Benson: None. G. Lanzino: None. W. Brinjikji: None.